Analysis of Factors Affecting Cash Holding in Technology Companies Listed on the Indonesia Stock Exchange for the Period 2020-2024 - dian melisa; Ramses Pakpahan (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2026)
Purpose – This study aims to determine the effects of Capital Expenditure, Sales Growth, Liquidity, and Cash Flow on Cash Holding Design/methodology/approach – This research uses quantitative data and consists of a sample of 14 Technology Companies listed on the Indonesia Stock Exchange from 2020 to 2024. Multiple regression analysis using EViews 9 Software was used to test the hypothesis Findings – The results indicate that Capital Expenditure has a negative and statistically insignificant effect on cash holdings, sales growth has a positive and statistically significant effect, liquidity has a positive and statistically significant effect, and cash flow has a positive and statistically significant effect Research limitations/implications – This research hopes to provide information on cash holdings and offer benefits in decision-making, as well as serve as a reference for further research